Direct chirp measurement in vector space of electroabsorption modulator - Mankong,U. (2015)
© 2014 IEICE. We propose a novel method to measure chirp of an electro-absorption modulator in vector space due to intensity modulation at any frequency using optical homodyne quadrature demodulation technique. Chirp parameters are directly obtained in the small-signal vector space, enabling practical chirp assessment for advanced modulation optical transmission.